Preparation method of a composition containing uridine and its application in treating developmental epileptic encephalopathy type 50
By preparing high-efficiency disintegrant and uridine complex and using spray coating technology, the problems of large weight differences, easy coating peeling, insufficient hardness and slow disintegration of uridine tablets in preparation, storage and transportation are solved, and the stability and efficient disintegration of uridine-containing compositions are achieved.
Patent Information
- Application Number
- CN202411406501.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-10
AI Technical Summary
In the preparation, storage and transportation of existing uridine tablets, there are problems such as large weight differences, easy coating peeling, insufficient hardness and slow disintegration speed.
The method of preparing disintegrant is adopted, including preparing aqueous phase, oil phase, crosslinking, primary modification and secondary modification, forming an efficient disintegrant and combining with the uridine complex, improving the binding amount and fluidity of uridine through surface treatment and loading technology, and finally preparing a uridine-containing composition through spray coating technology.
The prepared uridine-containing composition has achieved a small weight difference, high hardness, stable coating, fast disintegration speed and high dissolution, and is suitable for the treatment of developmental epilepsy encephalopathy type 50.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of pharmaceutical compositions, and in particular to a method for preparing a composition containing uridine and application of the composition in treating developmental epileptic encephalopathy type 50. Background Art
[0002] Uridine (UR) is a pyrimidine nucleoside and a key precursor of pyrimidine metabolism. It is a pyrimidine nucleoside necessary for the synthesis of RNA. It is composed of uracil and ribose connected by a β-N1-glycosidic bond and exists in plasma and cerebrospinal fluid. Uridine is involved in a variety of physiological processes, including RNA synthesis, glycogen synthesis, lipid deposition, etc. These factors work together to regulate the concentration of uridine and maintain a relatively stable state. Uridine is closely related to the body's homeostasis and participates in the regulation of glucose, lipid, amino acid metabolism and other metabolic processes. Abnormal uridine metabolism can lead to a variety of diseases, mainly epilepsy and neuropsychiatric damage. Some patients have orotic aciduria.
[0003] The synthesis of uridine is mainly completed through the pyrimidine nucleotide synthesis pathway, which includes the de novo synthesis pathway and the salvage synthesis pathway. The de novo synthesis pathway uses simple small molecules such as glutamine, carbon dioxide, aspartic acid, etc. as starting materials, and gradually synthesizes uridine through a series of enzyme-catalyzed reactions; the salvage synthesis pathway is that cells synthesize uridine by recycling and reusing existing pyrimidine bases, orally ingesting uridine or uridine precursors. Therefore, when the de novo synthesis of uridine in the body is insufficient, it needs to be supplemented by consuming uridine-rich foods, uridine or its precursors.
[0004] The anabolism of uridine and pyrimidine anabolism are in the same metabolic pathway. Uridine-5'-monophosphate is the central metabolite of pyrimidine anabolism and the precursor of all pyrimidine nucleotides. Pyrimidine nucleotides are essential substances for the synthesis of DNA and RNA, and play a key role in protein glycosylation, lipid metabolism, polysaccharide biosynthesis, signal transduction and proliferation. Enzyme defects in the de novo synthesis pathway can lead to a variety of diseases, such as developmental epileptic encephalopathy type 50. Developmental epileptic encephalopathy type 50 is a rare disease caused by functional defects in the CAD gene. The CAD gene is located at 2p23.3 and includes 44 exons. The encoded protein has four catalytic enzyme activities, namely, glutaminase, carbamoyl phosphate synthetase II, dihydroorotase, and aspartate transcarbamylase, which can catalyze the first three steps in the de novo synthesis pathway of uridine-5'-monophosphate. CAD gene functional defects can lead to decreased activities of glutaminase, carbamoyl phosphate synthetase II, dihydroorotase, and aspartate transcarbamylase, resulting in disorders in the first three steps of the de novo synthesis of uridine-5'-monophosphate, leading to abnormal uridine metabolism. One of the effective methods reported for developmental epileptic encephalopathy type 50 is oral administration of uridine.
[0005] Uridine, also known as uridine nucleoside, has a molecular formula of C9H 12 N2O6 is a white needle-shaped crystal or powder, odorless, slightly sweet and slightly pungent, and is a type of nucleoside. It is soluble in water, slightly soluble in dilute alcohol, insoluble in anhydrous ethanol, and has hygroscopicity. In order to facilitate taking, carrying, and storage, uridine needs to be made into a preparation. Considering the hygroscopicity of uridine, uridine is generally pressed into tablets to form cores, and then coated to form coated tablets.
[0006] However, in the process of making uridine into tablets and coating them, the following problems exist: 1) Since uridine is a needle-shaped crystal or powder with poor fluidity, the weight difference of the prepared coated tablets is large; 2) Since uridine is hygroscopic, a film coating is generally used for coating, but the adhesion between the film coating and the tablet core is poor, resulting in easy peeling of the film coating during preparation, storage and transportation; 3) After oral administration of uridine, uridine is degraded into uracil and ribose by digestive enzymes and then absorbed by the human body. Therefore, in order to improve the utilization efficiency of uridine, a large amount of disintegrant needs to be added to the tablet core. However, adding a large amount of disintegrant will cause the hardness of the coated tablets to decrease, making them easy to break or deform during preparation and transportation, and will also affect the fluidity of the raw materials in the tablet press, further resulting in large weight differences of the prepared coated tablets. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a method for preparing a composition containing uridine and application of the composition in the treatment of developmental epileptic encephalopathy type 50. The prepared uridine-containing composition has a small weight difference and high hardness. The coating is not easy to peel off during preparation, storage and transportation. It is not easy to break and deform during preparation and transportation, and has a fast disintegration speed.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a composition containing uridine, comprising the following steps: preparing a disintegrant, preparing a uridine complex, preparing a tablet core, preparing a coating solution, and coating;
[0010] The preparation of the disintegrant comprises the following steps: preparing an aqueous phase, preparing an oil phase, cross-linking, primary modification, and secondary modification;
[0011] The aqueous phase is prepared by adding potato starch and distilled water into a reactor, controlling the temperature of the reactor to 30-40° C., controlling the stirring speed to 200-400 rpm, stirring for 20-30 min, dripping sodium hydroxide aqueous solution into the reactor until the pH value is 8-8.5, and after the dripping is completed, controlling the temperature of the reactor to 75-85° C., stirring for 50-60 min, and obtaining an aqueous phase;
[0012] In the preparation of the aqueous phase, the mass ratio of potato starch to distilled water is 200-210:1000-1300;
[0013] The mass concentration of the sodium hydroxide aqueous solution is 10%;
[0014] The dropping speed of the sodium hydroxide aqueous solution is 1 to 1.5 g / min;
[0015] The oil phase is prepared by adding Span 60 and soybean oil into a reactor, controlling the temperature of the reactor to 55-65° C., controlling the stirring speed to 200-400 rpm, and stirring for 50-60 minutes to obtain an oil phase;
[0016] In the prepared oil phase, the mass ratio of Span 60 to soybean oil is 150-160:2600-3000;
[0017] The cross-linking comprises adding the oil phase into a reactor, controlling the temperature of the reactor to 15-35° C., controlling the stirring speed to 300-500 rpm, then dripping the water phase, continuing to stir for 40-60 min after the dripping is completed, adding sodium trimetaphosphate, continuing to stir for 6-7 h, adding into a centrifuge, controlling the centrifugal speed of the centrifuge to 10000-11000 rpm, centrifuging for 9-10 min, washing the precipitate with ethyl acetate 2-4 times, washing the precipitate with anhydrous ethanol 2-4 times, and drying to obtain cross-linked starch microspheres;
[0018] In the cross-linking, the mass ratio of the oil phase, the water phase, and the sodium trimetaphosphate is 2700-3100:1200-1400:10-12;
[0019] The dropping speed of the aqueous phase is 30-35 g / min;
[0020] The primary modification comprises adding sodium carboxymethyl starch and the first portion of distilled water into a reactor, controlling the temperature of the reactor to 15-35° C., controlling the stirring speed to 300-500 rpm, stirring for 20-30 min, then adding cross-linked starch microspheres, continuing stirring for 60-80 min, adding into a centrifuge, controlling the centrifugal speed of the centrifuge to 10000-11000 rpm, centrifuging for 9-10 min, washing the precipitate 3-4 times with distilled water, and then adding into a reactor with the second portion of distilled water, controlling the temperature of the reactor to 15-35° C., controlling the stirring speed to 300-500 rpm, stirring for 20-30 min, then adding sodium trimetaphosphate, continuing stirring for 4-5 h, adding into a centrifuge, controlling the centrifugal speed of the centrifuge to 10000-11000 rpm, centrifuging for 9-10 min, washing the precipitate 3-4 times with distilled water, and drying to obtain the primary modified microspheres;
[0021] In the one modification, the mass ratio of sodium carboxymethyl starch, the first portion of distilled water, cross-linked starch microspheres, the second portion of distilled water, and sodium trimetaphosphate is 20-25:5600-6000:290-310:5500-6000:5-6;
[0022] The secondary modification comprises adding sodium alginate and distilled water into a reactor, controlling the temperature of the reactor to 50-60° C., controlling the stirring speed to 300-500 rpm, stirring for 40-50 min, then adding cross-linked starch microspheres, continuing stirring for 60-80 min, adding into a centrifuge, controlling the centrifugal speed of the centrifuge to 11000-12000 rpm, centrifuging for 9-10 min, washing the precipitate with distilled water for 3-4 times, and drying to obtain a disintegrant;
[0023] In the secondary modification, the mass ratio of sodium alginate, distilled water, and cross-linked starch microspheres is 23-26:5600-6000:290-310;
[0024] The preparation of the uridine complex comprises the following steps: surface treatment and loading;
[0025] The surface treatment comprises adding polyethylene glycol 4000 and distilled water into a reaction kettle, controlling the temperature of the reaction kettle to 55-65° C., controlling the stirring speed to 300-500 rpm, stirring for 50-60 min, adding magnesium stearate, continuing stirring for 4-5 h, filtering, washing the filter residue with distilled water for 2-3 times, and drying to obtain surface-treated magnesium stearate;
[0026] In the surface treatment, the mass ratio of polyethylene glycol 4000, distilled water and magnesium stearate is 10-11:2000-2500:110-120;
[0027] The loading, adding polyethylene glycol 400, uridine and distilled water into a reaction kettle, controlling the temperature of the reaction kettle to 35-50° C., controlling the stirring speed to 300-500 rpm, stirring for 40-50 min, adding surface-treated magnesium stearate, continuing stirring for 3-4 h, filtering, washing the filter residue with distilled water for 2-3 times, and drying to obtain a uridine complex;
[0028] In the load, the mass ratio of polyethylene glycol 400, uridine, distilled water, and surface-treated magnesium stearate is 20-23:30-35:3600-4000:110-120;
[0029] In the preparation of the tablet core, the uridine complex, the disintegrant, hydroxypropyl methylcellulose and magnesium stearate are uniformly mixed and then tableted to obtain the tablet core;
[0030] In the preparation of the tablet core, the mass ratio of the uridine complex, the disintegrant, the hydroxypropyl methylcellulose and the magnesium stearate is 180-200:40-45:30-35:50-55;
[0031] The tableting pressure is 7 to 8 kN;
[0032] The weight of the tablet core is 440-450 mg;
[0033] The coating solution is prepared by adding hydroxypropyl methylcellulose, polyethylene glycol 400, titanium dioxide, polyvinyl pyrrolidone and distilled water into a reaction kettle, controlling the temperature of the reaction kettle to 15-40° C., controlling the stirring speed to 500-600 rpm, and stirring for 60-90 minutes to obtain a coating solution;
[0034] In the preparation of the coating solution, the mass ratio of hydroxypropyl methylcellulose, polyethylene glycol 400, titanium dioxide, polyvinyl pyrrolidone and distilled water is 30-40:8-10:13-15:14-17:1000-1100;
[0035] The coating comprises adding the tablet core into a fluidized bed coating machine, controlling the temperature of the fluidized bed coating machine to 50-55° C., keeping the temperature for 8-10 minutes, and spraying the tablet core with a coating liquid to obtain a composition containing uridine;
[0036] In the coating, the spray rate of the spray coating is 270-300 mL / h, and the coating weight gain is 2.9-3%.
[0037] A use of a uridine-containing composition obtained according to the aforementioned preparation method in the treatment of developmental epileptic encephalopathy type 50.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The preparation method of the composition containing uridine of the present invention comprises adding a disintegrant and a uridine complex in the preparation of the tablet core, wherein the preparation method of the disintegrant comprises preparing an aqueous phase, preparing an oil phase, cross-linking, primary modification, and secondary modification, wherein the purpose of preparing an aqueous phase, preparing an oil phase, and cross-linking is to prepare cross-linked starch microspheres, and then performing a primary modification on the surface of the cross-linked starch microspheres, specifically, after sodium carboxymethyl starch is adsorbed on the surface of the cross-linked starch microspheres, sodium trimetaphosphate is used for cross-linking to obtain cross-linked starch microspheres coated with cross-linked sodium carboxymethyl starch, i.e., primary modified microspheres, and finally performing a secondary modification on the surface of the cross-linked starch microspheres. The surface of the first modified microsphere is modified for the second time, specifically, sodium alginate is adsorbed on the surface of the first modified microsphere to obtain a disintegrant. After the uridine-containing composition is orally taken, the sodium alginate, cross-linked sodium carboxymethyl cellulose, and cross-linked starch microspheres absorb water and swell respectively, and the water absorption and swelling times are different. The innermost starch microspheres have a large water absorption and swelling times, so they can swell and disintegrate quickly, thereby improving the disintegration rate of the uridine-containing composition; disintegrants with different water absorption and swelling times are compounded to form microspheres, which can improve the fluidity of the disintegrant and reduce the weight difference of the prepared uridine-containing composition. The sodium alginate of the outer layer can improve the bonding force between the disintegrant and other raw materials, thereby ensuring that the coating is not easy to peel off during preparation, storage and transportation, and is not easy to break and deform during preparation and transportation, and has high hardness; the preparation method of the uridine complex includes surface treatment and loading, wherein the surface treatment is to use macromolecular polyethylene glycol 4000 to surface treat magnesium stearate, and a layer of macromolecular polyethylene glycol 4000 is coated on the surface of magnesium stearate to obtain surface-treated magnesium stearate, and the loading is to use small molecule polyethylene glycol and uridine to surface treat the surface-treated magnesium stearate, and the small molecule polyethylene glycol and uridine are coated on the surface of magnesium stearate. The glycoside is bound to the surface of the surface-treated magnesium stearate, and the macromolecular polyethylene glycol, the small molecule polyethylene glycol, and the uridine interact with each other, thereby increasing the binding amount and fluidity of the uridine and reducing the weight difference of the prepared uridine-containing composition; after oral administration of the uridine-containing composition, the small molecule polyethylene glycol can promote the release of uridine, thereby increasing the disintegration rate of the uridine-containing composition; and the small molecule polyethylene glycol can also increase the binding force between the uridine complex and other raw materials, thereby ensuring that the coating is not easy to peel off during preparation, storage, and transportation, and is not easy to break and deform during preparation and transportation, and has high hardness;
[0040] (2) The method for preparing the uridine-containing composition of the present invention has a small weight difference of the prepared uridine-containing composition, which is -1.1 to 1.2%;
[0041] (3) The method for preparing the uridine-containing composition of the present invention has high hardness, and the hardness of the prepared uridine-containing composition is 5.2 to 5.4 kg;
[0042] (4) The preparation method of the uridine-containing composition of the present invention is that the coating is not easy to peel off during preparation, storage and transportation, and is not easy to break and deform during preparation and transportation. According to the preparation method of the present invention, 1000 tablets of the uridine-containing composition are prepared. During preparation, 3 to 4 tablets peel off, 2 to 3 tablets break, and 3 to 6 tablets are deformed. After the uridine-containing composition that is peeled off, broken, and deformed is selected, a simulated transportation test is performed. After the test, the number of peeled tablets is 2 to 3, the number of broken tablets is 0 to 1, and the number of deformed tablets is 3 to 4; the uridine-containing composition prepared by the present invention is stored in an environment with a temperature of 40°C and a relative humidity of 75%. After storage for 1 month, the surface is intact;
[0043] (5) The preparation method of the uridine-containing composition of the present invention has a fast disintegration speed, and the disintegration time is 9min54s to 10min12s;
[0044] (6) The method for preparing the uridine-containing composition of the present invention has a high solubility. According to the second method of the dissolution determination method in Appendix XC of the 2010 edition of the Chinese Pharmacopoeia, with distilled water as the dissolution medium and a rotation speed of 50 revolutions per minute, the solubility at 45 minutes can reach 99.1-99.5%. Therefore, when the uridine-containing composition prepared by the present invention is used to treat developmental epileptic encephalopathy type 50, the release of uridine is not affected. DETAILED DESCRIPTION
[0045] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0046] Example 1
[0047] A method for preparing a composition containing uridine, specifically comprising:
[0048] 1. Preparation of disintegrant:
[0049] (1) preparing an aqueous phase: adding 200 g of potato starch and 1000 g of distilled water into a reactor, controlling the temperature of the reactor to 30° C., controlling the stirring speed to 200 rpm, stirring for 20 min, and dripping a 10% sodium hydroxide aqueous solution into the reactor until the pH value is 8, controlling the dripping speed of the sodium hydroxide aqueous solution to 1 g / min, and after the dripping is completed, controlling the temperature of the reactor to 75° C., stirring for 50 min, and obtaining an aqueous phase;
[0050] (2) Preparation of oil phase: Add 150 g of Span 60 and 2600 g of soybean oil into a reactor, control the temperature of the reactor to 55° C., control the stirring speed to 200 rpm, and stir for 50 min to obtain an oil phase;
[0051] (3) Cross-linking: 2700 g of the oil phase was added to a reactor, the temperature of the reactor was controlled to 15°C, the stirring speed was controlled to 300 rpm, and then 1200 g of the water phase was added dropwise at a rate of 30 g / min. After the addition was completed, stirring was continued for 40 min. 10 g of sodium trimetaphosphate was added and stirring was continued for 6 h. The mixture was added to a centrifuge and the centrifugal speed was controlled to 10,000 rpm. The mixture was centrifuged for 9 min. The precipitate was washed twice with ethyl acetate and twice with anhydrous ethanol, and then dried to obtain cross-linked starch microspheres.
[0052] (4) Primary modification: 20 g sodium carboxymethyl starch and 5600 g distilled water were added to a reactor, the temperature of the reactor was controlled to 15 ° C, the stirring speed was controlled to 300 rpm, and the mixture was stirred for 20 min. Then, 290 g cross-linked starch microspheres were added and the mixture was stirred for 60 min. The mixture was added to a centrifuge and the centrifugal speed was controlled to 10,000 rpm. The mixture was centrifuged for 9 min. The precipitate was washed with distilled water for 3 times and then added to a reactor with 5500 g distilled water. The temperature of the reactor was controlled to 15 ° C, the stirring speed was controlled to 300 rpm, and the mixture was stirred for 20 min. Then, 5 g sodium trimetaphosphate was added and the mixture was stirred for 4 h. The mixture was added to a centrifuge and the centrifugal speed was controlled to 10,000 rpm. The mixture was centrifuged for 9 min. The precipitate was washed with distilled water for 3 times and then dried to obtain primary modified microspheres.
[0053] (5) Secondary modification: 23 g of sodium alginate and 5600 g of distilled water were added to a reactor, the temperature of the reactor was controlled to 50°C, the stirring speed was controlled to 300 rpm, and the mixture was stirred for 40 min. Then, 290 g of cross-linked starch microspheres were added, and the mixture was stirred for 60 min. The mixture was added to a centrifuge, and the centrifugal speed of the centrifuge was controlled to 11000 rpm. The mixture was centrifuged for 9 min. The precipitate was washed with distilled water for 3 times, and then dried to obtain a disintegrant.
[0054] 2. Preparation of uridine complex:
[0055] (1) Surface treatment: add 10 g of polyethylene glycol 4000 and 2000 g of distilled water into a reactor, control the temperature of the reactor to 55° C., control the stirring speed to 300 rpm, stir for 50 min, add 110 g of magnesium stearate, continue stirring for 4 h, filter, wash the filter residue twice with distilled water, and dry to obtain surface-treated magnesium stearate;
[0056] (2) Loading: Add 20 g of polyethylene glycol 400, 30 g of uridine, and 3600 g of distilled water into a reactor, control the temperature of the reactor to 35 °C, control the stirring speed to 300 rpm, stir for 40 min, add 110 g of surface-treated magnesium stearate, continue stirring for 3 h, filter, wash the filter residue twice with distilled water, and dry to obtain a uridine complex;
[0057] 3. Preparation of tablet core: The uridine complex, disintegrant, hydroxypropyl methylcellulose and magnesium stearate were mixed uniformly in a mass ratio of 180:40:30:50 and tableted under a tableting pressure of 7 kN to obtain a tablet core;
[0058] The weight of the tablet core is 440 mg;
[0059] 4. Prepare a coating solution: add hydroxypropyl methylcellulose, polyethylene glycol 400, titanium dioxide, polyvinyl pyrrolidone, and distilled water in a mass ratio of 30:8:13:14:1000 into a reactor, control the temperature of the reactor to 15°C, control the stirring speed to 500 rpm, and stir for 60 minutes to obtain a coating solution;
[0060] 5. Coating: Add the tablet cores into a fluidized bed coater, control the temperature of the fluidized bed coater to 50°C, keep warm for 8 minutes, spray-coat the tablet cores with the coating liquid, control the spray rate to 270 mL / h, and the coating weight gain to 2.9%. After the coating is completed, a composition containing uridine is obtained.
[0061] This embodiment also provides a use of a uridine-containing composition obtained according to the aforementioned preparation method in the treatment of developmental epileptic encephalopathy type 50.
[0062] Example 2
[0063] A method for preparing a composition containing uridine, specifically comprising:
[0064] 1. Preparation of disintegrant:
[0065] (1) preparing an aqueous phase: adding 205 g of potato starch and 1200 g of distilled water into a reactor, controlling the temperature of the reactor to 35° C., controlling the stirring speed to 300 rpm, stirring for 25 min, and dripping a 10% sodium hydroxide aqueous solution into the reactor until the pH value is 8.2, controlling the dripping speed of the sodium hydroxide aqueous solution to 1.2 g / min, and after the dripping is completed, controlling the temperature of the reactor to 80° C., stirring for 55 min, and obtaining an aqueous phase;
[0066] (2) Preparation of oil phase: Add 155 g of Span 60 and 2800 g of soybean oil into a reactor, control the temperature of the reactor to 60° C., control the stirring speed to 300 rpm, and stir for 55 min to obtain an oil phase;
[0067] (3) Cross-linking: 2900 g of the oil phase was added to a reactor, the temperature of the reactor was controlled to 25°C, the stirring speed was controlled to 400 rpm, and then 1300 g of the water phase was added dropwise at a rate of 32 g / min. After the addition was completed, stirring was continued for 50 min. 11 g of sodium trimetaphosphate was added and stirring was continued for 6.5 h. The mixture was added to a centrifuge and the centrifugal speed was controlled to 10,000 rpm. The mixture was centrifuged for 10 min. The precipitate was washed 3 times with ethyl acetate and 3 times with anhydrous ethanol, and then dried to obtain cross-linked starch microspheres.
[0068] (4) Primary modification: 22 g sodium carboxymethyl starch and 5800 g distilled water were added to a reactor, the temperature of the reactor was controlled to 25 ° C, the stirring speed was controlled to 400 rpm, and the stirring was continued for 25 min. Then, 300 g cross-linked starch microspheres were added, and the stirring was continued for 70 min. The microspheres were added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 10000 rpm, and the microspheres were centrifuged for 10 min. The precipitate was washed with distilled water for 3 times, and then 5800 g distilled water was added to a reactor, the temperature of the reactor was controlled to 25 ° C, the stirring speed was controlled to 400 rpm, and the microspheres were stirred for 25 min. Then, 5.5 g sodium trimetaphosphate was added, and the stirring was continued for 4.5 h. The microspheres were added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 10000 rpm, and the microspheres were centrifuged for 10 min. The microspheres were washed with distilled water for 3 times, and then dried to obtain primary modified microspheres.
[0069] (5) Secondary modification: 25 g of sodium alginate and 5800 g of distilled water were added to a reactor, the temperature of the reactor was controlled to 55°C, the stirring speed was controlled to 400 rpm, and the stirring was performed for 45 min. Then, 300 g of cross-linked starch microspheres were added, and the stirring was continued for 70 min. The microspheres were added to a centrifuge, and the centrifugal speed of the centrifuge was controlled to 11000 rpm. The microspheres were centrifuged for 10 min. The precipitate was washed with distilled water for 3 times, and then dried to obtain a disintegrant.
[0070] 2. Preparation of uridine complex:
[0071] (1) Surface treatment: 10.5 g of polyethylene glycol 4000 and 2200 g of distilled water were added to a reactor, the temperature of the reactor was controlled to 60° C., the stirring speed was controlled to 400 rpm, and the stirring was continued for 55 min. 115 g of magnesium stearate was added, and the stirring was continued for 4.5 h. The residue was filtered, and the filter residue was washed twice with distilled water and dried to obtain surface-treated magnesium stearate.
[0072] (2) Loading: Add 22 g of polyethylene glycol 400, 32 g of uridine, and 3800 g of distilled water into a reactor, control the temperature of the reactor to 45 °C, control the stirring speed to 400 rpm, stir for 45 min, add 115 g of surface-treated magnesium stearate, continue stirring for 3.5 h, filter, wash the filter residue twice with distilled water, and dry to obtain a uridine complex;
[0073] 3. Preparation of tablet core: The uridine complex, disintegrant, hydroxypropyl methylcellulose and magnesium stearate were mixed evenly in a mass ratio of 190:42:32:52 and tableted under a tableting pressure of 8 kN to obtain a tablet core;
[0074] The weight of the tablet core is 450 mg;
[0075] 4. Prepare a coating solution: add hydroxypropyl methylcellulose, polyethylene glycol 400, titanium dioxide, polyvinyl pyrrolidone, and distilled water in a mass ratio of 35:9:14:15:1050 into a reactor, control the temperature of the reactor to 25°C, control the stirring speed to 600 rpm, and stir for 80 minutes to obtain a coating solution;
[0076] 5. Coating: Add the tablet cores into a fluidized bed coater, control the temperature of the fluidized bed coater to 52°C, keep warm for 9 minutes, spray-coat the tablet cores with the coating liquid, control the spray rate to 280 mL / h, and the coating weight gain to 3%. After the coating is completed, a composition containing uridine is obtained.
[0077] This embodiment also provides a use of a uridine-containing composition obtained according to the aforementioned preparation method in the treatment of developmental epileptic encephalopathy type 50.
[0078] Example 3
[0079] A method for preparing a composition containing uridine, specifically comprising:
[0080] 1. Preparation of disintegrant:
[0081] (1) preparing an aqueous phase: adding 210 g of potato starch and 1300 g of distilled water into a reactor, controlling the temperature of the reactor to 40° C., controlling the stirring speed to 400 rpm, stirring for 30 min, and dripping a 10% sodium hydroxide aqueous solution into the reactor until the pH value is 8.5, controlling the dripping speed of the sodium hydroxide aqueous solution to 1.5 g / min, and after the dripping is completed, controlling the temperature of the reactor to 85° C., stirring for 60 min, and obtaining an aqueous phase;
[0082] (2) Preparation of oil phase: Add 160 g of Span 60 and 3000 g of soybean oil into a reactor, control the temperature of the reactor to 65° C., control the stirring speed to 400 rpm, and stir for 60 min to obtain an oil phase;
[0083] (3) Cross-linking: 3100 g of the oil phase was added to a reactor, the temperature of the reactor was controlled to 35°C, the stirring speed was controlled to 500 rpm, and then 1400 g of the water phase was added dropwise at a rate of 35 g / min. After the addition was completed, stirring was continued for 60 min. 12 g of sodium trimetaphosphate was added and stirring was continued for 7 h. The mixture was added to a centrifuge and the centrifugal speed was controlled to 11000 rpm. The mixture was centrifuged for 10 min. The precipitate was washed with ethyl acetate 4 times and with anhydrous ethanol 4 times. The mixture was dried to obtain cross-linked starch microspheres.
[0084] (4) Primary modification: 25 g sodium carboxymethyl starch and 6000 g distilled water were added to a reactor, the temperature of the reactor was controlled to 35 ° C, the stirring speed was controlled to 500 rpm, and the stirring was continued for 30 min. Then, 310 g cross-linked starch microspheres were added, and the stirring was continued for 80 min. The microspheres were added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 11000 rpm, and the microspheres were centrifuged for 10 min. The precipitate was washed with distilled water for 4 times, and then added to a reactor with 6000 g distilled water. The temperature of the reactor was controlled to 35 ° C, the stirring speed was controlled to 500 rpm, and the microspheres were stirred for 30 min. Then, 6 g sodium trimetaphosphate was added, and the stirring was continued for 5 h. The microspheres were added to a centrifuge, the centrifugal speed of the centrifuge was controlled to 11000 rpm, and the microspheres were centrifuged for 10 min. The precipitate was washed with distilled water for 4 times, and then dried to obtain primary modified microspheres.
[0085] (5) Secondary modification: 26 g of sodium alginate and 6000 g of distilled water were added to a reactor, the temperature of the reactor was controlled to 60°C, the stirring speed was controlled to 500 rpm, and the mixture was stirred for 50 min. Then, 310 g of cross-linked starch microspheres were added, and the mixture was stirred for 80 min. The mixture was added to a centrifuge, and the centrifugal speed of the centrifuge was controlled to 12000 rpm. The mixture was centrifuged for 10 min. The precipitate was washed with distilled water for 4 times, and then dried to obtain a disintegrant.
[0086] 2. Preparation of uridine complex:
[0087] (1) Surface treatment: 11 g of polyethylene glycol 4000 and 2500 g of distilled water were added to a reactor, the temperature of the reactor was controlled to 65° C., the stirring speed was controlled to 500 rpm, and the stirring was performed for 60 min. 120 g of magnesium stearate was added, and the stirring was continued for 5 h. The residue was filtered, and the filter residue was washed with distilled water for 3 times, and dried to obtain surface-treated magnesium stearate.
[0088] (2) Loading: Add 23 g of polyethylene glycol 400, 35 g of uridine, and 4000 g of distilled water into a reactor, control the temperature of the reactor to 50 ° C, control the stirring speed to 500 rpm, stir for 50 min, add 120 g of surface-treated magnesium stearate, continue stirring for 4 h, filter, wash the filter residue with distilled water 3 times, and dry to obtain a uridine complex;
[0089] 3. Preparation of tablet core: uridine complex, disintegrant, hydroxypropyl methylcellulose and magnesium stearate are mixed evenly in a mass ratio of 200:45:35:55 and tableted under a tableting pressure of 7 to 8 kN to obtain a tablet core;
[0090] The weight of the tablet core is 450 mg;
[0091] 4. Prepare a coating solution: add hydroxypropyl methylcellulose, polyethylene glycol 400, titanium dioxide, polyvinyl pyrrolidone, and distilled water in a mass ratio of 40:10:15:17:1100 into a reactor, control the temperature of the reactor to 40°C, control the stirring speed to 600 rpm, and stir for 90 minutes to obtain a coating solution;
[0092] 5. Coating: Add the tablet cores into a fluidized bed coater, control the temperature of the fluidized bed coater to 55°C, keep warm for 10 minutes, spray-coat the tablet cores with the coating liquid, control the spray speed to 300 mL / h, and the coating weight gain to 3%. After coating, a composition containing uridine is obtained.
[0093] This embodiment also provides a use of a uridine-containing composition obtained according to the aforementioned preparation method in the treatment of developmental epileptic encephalopathy type 50.
[0094] Example 4
[0095] The difference between Example 4 and Example 2 is that Example 4 omits the first step of preparing the disintegrant, and in the third step of preparing the tablet core, sodium carboxymethyl starch is used instead of the disintegrant.
[0096] Example 5
[0097] The difference between Example 5 and Example 2 is that Example 5 omits the step 2 of preparing the uridine complex, and uses uridine instead of the uridine complex in the step 3 of preparing the core, and controls the mass ratio of uridine, disintegrant, hydroxypropyl methylcellulose and magnesium stearate to 36:42:32:52.
[0098] Test Example 1
[0099] According to the preparation methods of the uridine-containing compositions of Examples 1-5, 1000 pieces of uridine-containing compositions were prepared, and the uridine-containing compositions that were peeled, broken, and deformed were selected and counted. Then, 20 pieces were randomly selected, and the weight difference and hardness were tested. The average hardness was calculated. The results are as follows:
[0100]
[0101] Then, simulated transportation tests were conducted separately, specifically, the remaining uridine-containing compositions were added to containers, the containers were sealed and mechanically oscillated, the frequency of the mechanical oscillation was controlled to be 20 times / minute, the amplitude was 3 cm, and after 1000 mechanical oscillations, the number of uridine-containing compositions that were peeled, broken, and deformed was counted, and the statistical results were as follows:
[0102]
[0103] Test Example 2
[0104] Six tablets of the uridine-containing composition obtained in Test Example 1 were taken respectively, and then the disintegration time was tested, and the average disintegration time was calculated. The calculation results are as follows:
[0105]
[0106] Test Example 3
[0107] The coating stability of the uridine-containing composition obtained in Test Example 1 was tested, and the test method and test results are as follows:
[0108] 100 pieces of the uridine-containing composition were taken respectively and stored in an environment with a temperature of 40°C and a relative humidity of 75%. After storage for 1 month, the surface of the uridine-containing composition was observed to see whether it was intact. The observation results were as follows:
[0109]
[0110] Test Example 4
[0111] The dissolution of Examples 1-5 was tested, and the test method and test results are as follows:
[0112] According to the second method of dissolution determination method in Appendix XC of the 2010 edition of the Chinese Pharmacopoeia, distilled water was used as the dissolution medium, the speed was 50 revolutions per minute, and the dissolution was tested at 45 minutes. The test results are as follows:
[0113]
[0114] It can be seen from the results of test examples 1-4 that Example 4, based on the preparation method of Example 2, uses sodium carboxymethyl starch and other substances instead of the disintegrant in the step of preparing the tablet core. There are problems such as large weight differences in the obtained uridine-containing composition, easy peeling of the coating during preparation, storage and transportation, breakage and deformation during preparation and transportation, slow disintegration rate, low hardness and poor dissolution effect.
[0115] Example 5 is based on the preparation method of Example 2, and uridine is used instead of the uridine complex in the step of preparing the core tablets. However, there are problems such as large weight difference of the uridine-containing composition obtained, easy peeling of the coating during preparation, storage and transportation, breakage and deformation during preparation and transportation, slow disintegration rate and low hardness.
[0116] Unless otherwise specified, all percentages used in the present invention are by mass.
[0117] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composition containing uridine, characterized in that: The method comprises the following steps: preparing a disintegrant, preparing a uridine complex, preparing a tablet core, preparing a coating liquid, and coating; The preparation of the disintegrant comprises the following steps: preparing an aqueous phase, preparing an oil phase, cross-linking, primary modification, and secondary modification; The aqueous phase is prepared by mixing potato starch and distilled water, stirring at 30-40° C., adjusting the pH to 8-8.5, and stirring at 75-85° C. after the dropwise addition to obtain an aqueous phase; The oil phase is prepared by mixing Span 60 and soybean oil, and stirring at 55-65° C. to obtain an oil phase; The cross-linking, controlling the oil phase to 15-35°C and stirring, then dropping the water phase, continuing to stir after the dropping, adding sodium trimetaphosphate, continuing to stir, centrifuging, washing, drying the precipitate, to obtain cross-linked starch microspheres; The primary modification comprises mixing sodium carboxymethyl starch and the first portion of distilled water, stirring at 15 to 35° C., then adding cross-linked starch microspheres, continuing stirring, centrifuging, washing the precipitate, mixing the precipitate with the second portion of distilled water, stirring at 15 to 35° C., then adding sodium trimetaphosphate, continuing stirring, centrifuging, washing, and drying the precipitate to obtain the primary modified microspheres; The secondary modification comprises mixing sodium alginate and distilled water, stirring at 50-60° C., adding cross-linked starch microspheres, continuing stirring, centrifuging, washing, drying the precipitate, and obtaining a disintegrant; The preparation of the uridine complex comprises the following steps: surface treatment and loading; The surface treatment comprises mixing polyethylene glycol 4000 and distilled water, stirring at 55-65° C., adding magnesium stearate, continuing stirring, filtering, washing, and drying the filter residue to obtain surface-treated magnesium stearate; The loading comprises mixing polyethylene glycol 400, uridine and distilled water, stirring at 35-50° C., adding surface-treated magnesium stearate, continuing stirring, filtering, washing and drying the filter residue to obtain a uridine complex; In the preparation of the tablet core, the uridine complex, the disintegrant, hydroxypropyl methylcellulose and magnesium stearate are uniformly mixed and then tableted to obtain the tablet core; The coating solution is prepared by mixing hydroxypropyl methylcellulose, polyethylene glycol 400, titanium dioxide, polyvinyl pyrrolidone and distilled water, and stirring at 15 to 40° C. to obtain a coating solution; The coating is performed by spraying the tablet core with a coating liquid at 50-55° C. to obtain a composition containing uridine.
2. The method for preparing the uridine-containing composition according to claim 1, characterized in that: In the preparation of the aqueous phase, the mass ratio of potato starch to distilled water is 200-210:1000-1300.
3. The method for preparing the uridine-containing composition according to claim 1, characterized in that: In the prepared oil phase, the mass ratio of Span 60 to soybean oil is 150-160:2600-3000.
4. The method for preparing the uridine-containing composition according to claim 1, characterized in that: In the cross-linking, the mass ratio of the oil phase, the water phase, and the sodium trimetaphosphate is 2700-3100:1200-1400:10-12; The dropping speed of the water phase is 30-35 g / min.
5. The method for preparing the uridine-containing composition according to claim 1, characterized in that: In the one modification, the mass ratio of sodium carboxymethyl starch, the first portion of distilled water, cross-linked starch microspheres, the second portion of distilled water, and sodium trimetaphosphate is 20-25:5600-6000:290-310:5500-6000:5-6.
6. The method for preparing the uridine-containing composition according to claim 1, characterized in that: In the secondary modification, the mass ratio of sodium alginate, distilled water and cross-linked starch microspheres is 23-26:5600-6000:290-310.
7. The method for preparing the uridine-containing composition according to claim 1, characterized in that: In the surface treatment, the mass ratio of polyethylene glycol 4000, distilled water and magnesium stearate is 10-11:2000-2500:110-120; In the load, the mass ratio of polyethylene glycol 400, uridine, distilled water and surface-treated magnesium stearate is 20-23:30-35:3600-4000:110-120.
8. The method for preparing the uridine-containing composition according to claim 1, characterized in that: In the preparation of the tablet core, the mass ratio of the uridine complex, the disintegrant, the hydroxypropyl methylcellulose and the magnesium stearate is 180-200:40-45:30-35:50-55; The tableting pressure is 7 to 8 kN; The weight of the tablet core is 440-450 mg.
9. The method for preparing the uridine-containing composition according to claim 1, characterized in that: In the preparation of the coating solution, the mass ratio of hydroxypropyl methylcellulose, polyethylene glycol 400, titanium dioxide, polyvinyl pyrrolidone and distilled water is 30-40:8-10:13-15:14-17:1000-1100; In the coating, the spray rate of the spray coating is 270-300 mL / h, and the coating weight gain is 2.9-3%.
Citation Information
Patent Citations
Oral formulations of cytidine analogs and methods of use thereof
CN103479586A
Medicine preparation containing 5-fluorouracil drug eutectic with nicotinamide as precursor and preparation method of medicine preparation
CN105732517A